2020
DOI: 10.1371/journal.pone.0230017
|View full text |Cite
|
Sign up to set email alerts
|

Amsler grid test for detection of advanced glaucoma in Ethiopia

Abstract: This study was done to determine the validity of amsler grid test black on white (BOW), as well as white on black (WOB) for identifying central visual field (VF) defects in patients with advanced glaucoma. Design Prospective study. Participants We prospectively included 100 consecutive eyes of 88 adult patients with advanced glaucoma and 100 eyes of 100 normal individuals. We used a lottery method to choose the side of the eye for the control groups. Methods All participants had reliable Humphrey 10-2 Swedish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Such tests range from relatively sophisticated technologies, such as tonometers, to growingly available functional technologies, such as perimetry and Amsler grid tests. [19][20][21][22][23][24] Bene ts have also been observed from early treatment and identi cation of AMD and DR using manual ophthalmoscopy or portable fundus photography and Amsler grid testing. 25 Given that many neurologic and endocrine conditions manifest in the eyes, multimodal vision testing tools such as color vision and scotoma testing can enhance a screening potential for these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Such tests range from relatively sophisticated technologies, such as tonometers, to growingly available functional technologies, such as perimetry and Amsler grid tests. [19][20][21][22][23][24] Bene ts have also been observed from early treatment and identi cation of AMD and DR using manual ophthalmoscopy or portable fundus photography and Amsler grid testing. 25 Given that many neurologic and endocrine conditions manifest in the eyes, multimodal vision testing tools such as color vision and scotoma testing can enhance a screening potential for these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As has been illustrated, AG has been shown to be effective in screening severe central vision loss in patients with glaucoma 14–16 . You would expect physicians to routinely suggest using AG in the management of severe glaucoma.…”
mentioning
confidence: 97%
“…Similar results were published by Gessesse et al in a series of patients from Ethiopia with advanced glaucoma. They also found high sensitivity and specificity in AG in detecting VF defects in these patients 15 . Fujitani et al demonstrated that a patient’s perception of glaucomatous visual field loss using an AG could be assessed 16 …”
mentioning
confidence: 97%
See 2 more Smart Citations